ARCHETYPICAL SOURCES OF PHENOMENON OF BETRAYAL IN UKRAINIAN MENTALITY - Карпенко, З. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with radical archetype in the Ukrainian mentality - a Mother archetype consisting of the aspects of a Custodian, a Temptated and a Deceived Woman. Difficulties of national and political self-determination of the Ukrainians (based on the collective unconscious «trap») can be explained by the deep intention to preserve the vital interests of the people and the ties of blood versus common values of the ethnos. Individualistic morals lead to the betrayal of the partners, allies, and eventually to the historical and civilizing defeat. The message of the article is the necessity to elaborate the vital ethnocultural narrative resisting archetypical tendencies of the social behaviour of the Ukrainians.